2015
DOI: 10.1097/mlr.0000000000000328
|View full text |Cite
|
Sign up to set email alerts
|

Health Care System-level Factors Associated With Performance on Medicare STAR Adherence Metrics in a Large, Integrated Delivery System

Abstract: Background:The Centers for Medicare and Medicaid Services provide significant incentives to health plans that score well on Medicare STAR metrics for cardiovascular disease risk factor medication adherence. Information on modifiable health system-level predictors of adherence can help clinicians and health plans develop strategies for improving Medicare STAR scores, and potentially improve cardiovascular disease outcomes.Objective:To examine the association of Medicare STAR adherence metrics with system-level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
71
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(81 citation statements)
references
References 25 publications
(22 reference statements)
5
71
0
Order By: Relevance
“…38,40,47 The remaining four studies considered (1) 30 days' versus 60 days' supply, 39 (2) 100 days' versus 34 days' supply, 44 (3) 90 days versus < 90 days' supply 37 and (4) prescription lengths of ≤ 90 days. 43 The number of medications examined in a single study ranged from one 40 to 'any medication for a chronic condition'.…”
Section: Systematic Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…38,40,47 The remaining four studies considered (1) 30 days' versus 60 days' supply, 39 (2) 100 days' versus 34 days' supply, 44 (3) 90 days versus < 90 days' supply 37 and (4) prescription lengths of ≤ 90 days. 43 The number of medications examined in a single study ranged from one 40 to 'any medication for a chronic condition'.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…35,37,[39][40][41]44,48,49 Ryvkin et al 38 did not report the length of their study. The most common outcomes measured were adherence, 35,36,39,40,[43][44][45]47 wastage 32,36,38,41,42,45,46,48 and costs. 42,[44][45][46]49 When the study design was not reported 35,36,38,43,46 or was unclear, 41,49 the design was classified by three reviewers (JE, SK and CMiani) based on the information presented, and guided by the NICE algorithm for classifying quantitative study designs.…”
Section: Systematic Reviewmentioning
confidence: 99%
See 3 more Smart Citations